Optimization Of Bread Distribution Transportation Costs At Ud Bakery Garden Using The MDMA Method (Maximum Divide Minimum Alloment) - Febrianti, Putri Rizky; Dur, Sajaratud; Aprilia, Rima (International Conference on Sciences Development and Technology, 2022)
This study aims to optimize distribution transportation costs using a transportation model. The transportation model is a model that aims to determine the number of goods that must be sent from source to destination so that total transportation costs can be optimized. The transportation model used in this study is the Maximum Divide Minimum Aloment (MDMA) method. Data collection is in progress using Maximum Divide Minimum Aloment (MDMA), namely data on fixed costs, variable costs, demand and capacity of goods. The results of optimization research using the Maximum Divide Minimum Aloment (MDMA) method were obtained at Rp. 24,541,890 and has a difference with the costs incurred by the company of Rp. 3,449,660. Therefore, the MDMA (Maximum Divide Minimum Aloment) method can solve problems or can be used to minimize transportation costs.